2019
DOI: 10.1007/s12288-019-01123-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytogenetic Abnormalities in Patients with Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) accounts for 20% of all adult leukemias and is the most common leukemia during childhood (80%). We present data on cytogenetics of ALL from a tertiary centre in India correlating it with clinical factors. Karyotyping of bone marrow samples of 204 patients with newly diagnosed ALL was performed with standard G-banding technique. Clinical data of patients was obtained from case records. Survival was estimated using Kaplan-Meir curves and compared by the log-rank test. Univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…16 Patients with t(9;22)Ph + chromosome are considered as high risk cytogenetic group and are associated with disease relapse. 14,18 In our patients t(9;22) Ph + was seen in adult (6.25%) age group only out of which 1.25% did not respond well to treatment. Reddy P et al reported the similar findings in Ph + patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…16 Patients with t(9;22)Ph + chromosome are considered as high risk cytogenetic group and are associated with disease relapse. 14,18 In our patients t(9;22) Ph + was seen in adult (6.25%) age group only out of which 1.25% did not respond well to treatment. Reddy P et al reported the similar findings in Ph + patients.…”
Section: Discussionmentioning
confidence: 54%
“…Reddy P et al reported 42% with hyper leukocytosis and the median age of paediatric group in his study was 8years whereas 26.5years in adult group. 14 To understand the genetic basis of ALL, cytogenetic has proved to be a very powerful tool over the years. Correlation of well-established cytogenetic abnormalities with age is strongly related to the disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The cytogenetic data of ALL cases showed chromosomal translocations t(9;15)(p13;q11.2), t(1;19)(q25;p13.3), t(9;22)(q34;q11.2), and hyperdiploidy with other abnormalities in B-cell ALL while hypodiploidy was noted in T-cell ALL cases. Several studies have identified the same chromosomal translocations and the presence of hypo and hyperdiploid chromosomes in ALL cases [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 98%
“…A study by Reddy et al (2019), evaluated genetic abnormalities in 204 patients with ALL. The most common karyotypes observed include normal karyotype in 39.7% (n = 81), hyperdiploidy in 12.7% (n = 26), t (9; 22) in 4.4% (n = 9), and t (1; 19) in 3.9%.…”
Section: Discussionmentioning
confidence: 99%